Management of Guidance and Counseling Services in The Merdeka Belajar Curriculum - Tri Cahyono (Bisma The Journal of Counseling, 2022)
Merdeka Belajar curriculum requires school counselors to innovate services to suit the characteristics of the curriculum. Merdeka Belajar curriculum places a lot of emphasis on strengthening students' character. The character strengthening is carried out through intracurricular activities that are included in learning in each subject, and through the Pancasila Student Profile Strengthening Project (P5) which takes place outside the learning session. The program implementer involves all members of the learning committee including school counselors. Guidance and counseling have an important role in the success of the independent learning curriculum. School counselors can take part in the implementation of the Proyek Penguatan Profil Pelajar Pancasila (Pancasila Student Profile Strengthening Project/P5), especially in developing student character. School counselors should be able to develop a P5 which is innovative and fun in strengthening students' character. In addition, school counselors can also arrange guidance and counseling programs that are able to develop the character of students in accordance with the ideals of an independent curriculum. This includes compiling an assessment to measure how far the level of achievement of student character in the school is. This article describes the role of school counselors in implementing the independent learning curriculum. This article is based on a study of the role and function of guidance and counseling in the independent learning curriculum implemented by the Ministry of Education, Culture, Research and Technology.